Biomechanics of alloplastic mandible reconstruction using biomaterials: The effect of implant design on stress concentration influences choice of material. (March 2020) - Prasadh, Somasundaram; Suresh, Santhosh; Hong, Kang Lun; Bhargav, Aishwarya; Rosa, Vinicius; Wong, Raymond Chung Wen
Abstract: Introduction: Mandibular endoprostheses have been explored extensively as potential methods of alloplastic reconstruction. Studies, however, have demonstrated that for segmental mandibular defects, there are challenges associated with loosening. Another method recently introduced in clinical settings is popular as a design for patient-specific implants for segmental mandibular defect and involves a tray (filled with bone) over the defect with wings on both sides secured with screws. Our aim was to investigate which design better withstands the forces of function since studies have presented favourable results with regard to the wing design. Materials and methods: Two designs, an endoprosthesis with stems and wings were modelled. Finite element analysis was performed, and geometric data obtained from a human-sized mandible. A continuity defect of 20 mm was created digitally at the right mandibular molar region and the modelled segments combined with the endoprosthesis. Boundary conditions were set, and 300-N vertical loads applied in the incisor region. The stress concentrations and displacements were evaluated for the titanium alloy (Group 1-Stem) (Group 2-Wing) and the polycaprolactone (PCL) (Group 3 with stem, Group 4 wing design). Results: For the titanium stem (Group 1), the stress values were in the 557–803 MPa range. The titanium wing (Group 2) design showed markedly reduced stress values in the 20–68 MPa range. The stresses observed for the PCL(Group 3) were in the 66–110 MPa range, and the stress concentration in the PCL wing (Group 4) was observed in the wing and body regions of the scaffolds in the 8–42 MPa range. Conclusion: The wing design decreased the areas of stress concentrations significantly compared to an endoprosthesis. PCL alone did not have adequate strength to withstand forces applied even in a design that reduced stress concentrations significantly.